Comprehensive equation-based design of photovoltaic module to investigate its physical parameters and operating conditions used for small application. (May 2020) - Saleem, Adeel; Liu, Nain; Junjie, Hu; Iqbal, Atif; Waqar, Ali
Solar photovoltaic is clean and green energy for renewable power generation, which plays a vital role to fulfil the power shortage for any region. Photovoltaic array is quite expensive and has non-linear characteristics. Under varying conditions, it takes much time to give operating curves. Before mount photovoltaic for any application or at any location, there is a vital phase of analysis, modelling, and simulation of the photovoltaic system, which helps to understand the actual behaviour in real conditions. This paper emphasizes on the stepwise procedure of modelling and simulation for the photovoltaic panel, which is proposed to use for the small application. The proposed system provides a reliable, accurate, and simple method to model the photovoltaic system. It takes a flexible solar panel of 180 W as a reference model. The I–V and P–V characteristics are further investigated at different operating conditions such as a variation of irradiance from 1000 to 400 W/m 2, variation of temperature from 15 to 70 °C, and vary shunt resistance from higher to low values. The equation-based modelling of the photovoltaic system is built in the MATLAB/Simulink. This methodology allows investigating the photovoltaic system on different operating conditions (varying temperature and irradiance) and physical parameters (ideality factor, series and shunt resistance) along with partial shading effect.